Analisis Struktur Pasar Bank Umum Swasta Nasional dan Bank Persero Periode Tahun 2014-2021 - Denizar, Tri Irvan; Sambodo, Herman; Gunawan, Ratna Setyawati (Lingka Ekonomika, 2023)
This research is a quantitative research using secondary data during the 2014- 2018 period which focuses on the market structure of national private commercial banks and state-owned banks. The problem in this research is that the banking industry in Indonesia is still concentrated in large banks, thus creating a market that is less competitive and causing monopolistic or oligopolistic behavior from banks that have dominance. The purpose of this study is to analyze the market structure of national private commercial banks and state-owned banks for the 2014- 2021 period. The data sources for this research were obtained from the official websites of Bank Indonesia (BI), the Financial Services Authority (OJK), and the financial statements of the banks that were used as research objects, totaling ten banks consisting of national private commercial banks and state-owned bank. The market structure of national private commercial banks and state-owned banks can be analyzed using the calculation of the Concentration Ratio (CR) and the Herfindal Hirschman Index (IHH). Based on result of research and data analysis it has got the conclusions that the market structure of national private commercial banks and state-owned banks in Indonesia tends to experience increased market concentration and is classified as concentrated or can be categorized as tight oligopoly competition.